PEMBERIAN BAHAN SILIKA PADA TANAH SAWAH BERKADAR P TOTAL TINGGI UNTUK MEMPERBAIKI KETERSEDIAAN P DAN Si TANAH, PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) - Orinda Yohana; Hamidah Hanum; Supriadi Supriadi (Universitas Sumatera Utara, 2013)
This study aims to know the effect of Si on the availability of soil phosphate and silica, rice growthand production in the paddys soil with high total P . The research was conducted on the greenhouseand on the laboratory soil chemistry, Faculty of Agriculture, University of North Sumatra, Medan.The soil which used from the paddys soil in Tanjung Mulia Hilir, Medan Deli which has the hightotal P. The experiment was carried out using non-factorial randomized block design with treatmentcontrol, 3.4 g silica agrosil fertilizer/ plant, 4.8 g silica agrosil fertilizer/ plant, husk ash 3.4 g/ plantand 4.8 g husk ash / plant. The Analysis of data used the analysis of variance and contrast test.Experimental results showed that silica materials has significant effect on soil pH, maximum tillernumber and dry weight of grain, but not significant effect on available P, available Si, P – uptake, Si– Uptake, Plant Height, and Plant Dry Weight. Husk ask and Agrosil silica showed the same effectin the soil chemistry nature that’s the soil phosphate and silica availability.Keyword : silica material, paddy Soil, P, Si – uptake, rice growth and production